PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA QUIZIZZ UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SEKOLAH DASAR - Syifa Alyadani; Dedi Sofyan; Epon Nurlaela (STKIP Subang, 2024)
This research aimed to enhance the critical thinking skills of fifth-grade students at Julang Public Elementary School in the second semester of the 2023/2024 academic year through the implementation of the Problem Based Learning (PBL) model using Quizizz as a media tool. The research employed a classroom action research design with two cycles, consisting of planning, implementation, observation, and reflection stages. The research subjects were 24 students from class V B at Julang Public Elementary School in the second semester of the 2023/2024 academic year. The research data consisted of formative assessment results conducted using Quizizz as the supporting media. The data were then analyzed descriptively. The success criteria for the research were achieved if the average learning outcomes reached at least 75, and the classical mastery percentage was at least 85%. The results of the study in the first cycle indicated a classical mastery percentage of 54.16%, while in the second cycle, the average learning outcome score for Social and Natural Science (SNS) was 82 with a classical mastery percentage of 87.5%. Thus, the success criteria of this research were achieved in the second cycle. The students' critical thinking skills showed improvement from the first cycle to the second cycle. The results of the study revealed that the implementation of the PBL model using Quizizz as a supporting media tool could enhance the critical thinking abilities of fifth-grade students.